The Effect Of Problem Based Learning (PBL) On Student’s Writing Skill Of The Eleventh Grade - Nandito Tampubolon; Mungkap M. Siaahan; Novra Melisa P. Hutabarat (Jurnal Ilmu Pendidikan dan Sosial, 2026)
Mastery of writing skills is very important. However, many students experience difficulties and challenges in improving their writing skills. This study was used to determine the effect of implementing the Problem Based Learning (PBL) model on the writing skills of class XI students of SMK Swasta GKPI 1 Pematangsiantar using a quantitative approach with a quasi-experimental design. This study took samples using a purposive sampling technique involving 60 students who were divided into 2 groups, namely the experimental group (XI TKJ A) which consisted of 30 students, and the control group (X TKJ B) which also consisted of 30 students. In this study, the experimental class received treatment using the Problem Based Learning (PBL) model and the control class with conventional methods. In this study, data were collected with pre-test and post-test and analyzed using an independent sample t-test where in the experimental class the mean pre-test value was 40,67 and post-test was 75, while the mean value in the control class on the pre-test was 35,33 and post-test was 50. After being tested using the t-test, a significance value (2-tailed) of 0.000 < 0.05 was obtained, so the Null Hypothesis (H0) was rejected and the Alternative Hypothesis (Ha) was accepted. This means that there was a significant increase in students in the experimental class who were given treatment. So, this shows a significant difference between the experimental class and the control class. Based on the research findings, it was concluded that the Problem Based Learning (PBL) model can significantly improve students' writing skills, especially in writing analytical texts with correct organization.